ANALISIS PENGARUH PENGUMUMAN LABA TERHADAP VOLUME PERDAGANGAN SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (BEI) - F, Dwi Septia; Dwitayanti, Yevi (Jurnal Manajemen dan Keuangan, 2012)
Money market is an activity dears with public companyâs general bargain and stock â trade which relates to its raised stock and both intitutions and professions which have relation with stock as well. The main requirement needed by the investors to channel their money through stock â exchange is their investationsâ safety. The investors confidence causes them conducting transactions in stock â exchange. That will be reflected in form of exchange indicators and characteristics such as stock â trade volume at rate of exchange, and so on. The research is done at manufacture companies since they develop well this year and the investors prefer this kind of companies is as much as not only most of the manufacture companiesâ stocks get undervalue, but also the exchange reaction in ten days before and after the profit announcement. The objectives of the research are to prove empirically the difference of stock â trade volume average before and after profit announcement at companies registered in BEI and the influence of dependent variable in this case stock â trade volume at those companies. Meanwhile, the research methodology used is library reseacrh by reading and analyzing literatures, scientific researchesand the result of research and observing secondary data provided at BEI as well. Then, data are analyzed by using quantitative analysis tool, while the analysis method used is a simple linear regression analysis. Finally, The result of the research successfully proves a significant result of ; first, stock- trade volume average before and after profit announcement proven by the test result T count is 5,717 higher than T table 2,042. Second, Profit announcement which has stock â trade proven by test result F count higher than F table, 7,207 higher than 4,17 with the signification rate 0,012 lower than 0,05. In short, the profit announcement effects the stock transaction change by the changing of stock â trade volume.Keywords: Profit Announcement Towad Stock â Trade Volume Of ManufactureCompanies